(untitled) (Research, Society and Development, 2021)
Objective: to evaluate the influence of the teaching-learning method on the perception of quality of life (QL) and stress among nursing students at a Brazilian federal university. Method: cross-sectional study carried out on two campuses of a public university, data collected through a questionnaire containing items for socioeconomic, academic and lifestyle habits, the WHOQOL-bref and the PSS-10, to assess QoL and perception of stress , respectively. Statistical analysis was performed using Fisher’s Exact, Chi-square, T-test, ANOVA and Pearson’s correlation tests. Results with p<0.05 were considered significant. Results: the sample consisted of 113 students from the active campus and 130 from the traditional campus, predominantly female (194;79.8%), non-white (183;75.3 %), with a mean age of 22.52±4.67 years, residing in the urban area (220.90.5%), who lived with their family (126;51.9%), did not exercise paid work (203;83.5%) and were enrolled in the first three years of the course (158; 65%). The global QoL had an average of 56.44±12.53 and the perception of stress was 23.99±6.71. Although there was no difference between the perception of stress, the active method students had better global QoL scores and in the psychological, social, and environmental domains (p<0.05). Conclusion: the active method students showed better results in the assessment of QoL, but there were no significant differences in the perception of stress between the evaluated groups.